Efecto antibacteriano in vitro del aceite esencial de cinnamomum zeylanicum (canela) sobre el fusobacterium nucleatum atcc 25586 - García Rubio, Khatteryne Marisol (2016)
The aim of the present research work was to determine in vitro the antibacterial effect of the essential oil of Cinnamomum zeylanicum (cinnamon) on Fusobacterium nucleatum ATCC 25586. The study was carried out in the laboratories of Pharmacognosy and microbiological laboratories in the School of Medicine at the National University of Trujillo. Samples consisted in two sets of 12 repeats for each concentration of cinnamon and sample control (penicillin). One set was used to determine the sensitivity or bacterial resistance, whereas the other set was used to determine the bactericidal effect. The effectiveness of the essential oil on Fusobacterium nucleatum ATCC 25586 was evaluated by two parameters: 1) the bacterial sensitivity, by using the disk diffusion method, in which inhibition halos, according to the Duraffourd scale, were found and 2) the bactericidal effect, by observing the presence or absence of Colony Forming Units (CFUs). The results show that the essential oil Cinnamomum zeylanicum (Cinnamon) has an in vitro antibacterial effect on Fusobacterium nucleatum ATCC 25586.